"Boys Are Running off to the Wars by Scores": Promoting Masculinity and Conquest in the Coverage of the Mexican-American War. Issue 2 (2nd April 2016) - Bernhardt, Mark
Abstract : Moses Yale Beach, publisher of the New York Sun, and James Gordon Bennett, publisher of the New York Herald, promoted the Mexican-American War through illustrations that linked conquest with the fulfillment of certain masculine ideals. Both were expansionists who wanted the United States to take Mexican land as spoils of war. But they differed in opinion on how much territory the United States should claim. Beach believed it best to take only the sparsely populated northern portion, whereas Bennett advocated conquering Mexico in its entirety. Consequently, there are important differences in the types of illustrations they published with their war reports that reflect their positions on land acquisition and its connection to the fulfillment of masculine ideals.